2011
DOI: 10.1007/s00586-011-1978-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the cross-sectional area of deep posterior extensor muscles of the cervical spine after anterior decompression and fusion: 10-year follow-up study using MRI

Abstract: Purpose To evaluate changes in the transverse area of deep posterior muscles of the cervical spine 10 years after anterior cervical decompression and fusion (ACDF), in comparison with healthy volunteers. Methods Thirty-one patients (22 males, 9 females, mean age at follow-up 59.3 years, mean follow-up 12.1 years) who had undergone preoperative MRI and non-instrumented ACDF within levels C3-4 to C5-6 were enrolled. 32 asymptomatic volunteers (17 males, 15 females; mean age, 54.7 years; mean follow-up, 11.7 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…In the present study, women had significant smaller muscle volumes than men for all measured muscles at all levels analogous to the findings of Matsumoto et al (11) and Okada et al (12). The fact that women suffer more often from whiplash injury (13) is well known.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, women had significant smaller muscle volumes than men for all measured muscles at all levels analogous to the findings of Matsumoto et al (11) and Okada et al (12). The fact that women suffer more often from whiplash injury (13) is well known.…”
Section: Discussionsupporting
confidence: 92%
“…According to our search, eleven studies were found, four of which were prospective and seven retrospective. Six studies were concentrated on anterior approaches (Table 1 [19][20][21][22][23]) and five studies on posterior approaches in the cervical spine (Table 2 [24][25][26][27][28][29]).…”
Section: Resultsmentioning
confidence: 99%
“…No significant association was observed between neck pain and changes in the cross-sectional area of the posterior muscles over time. Thus, they demonstrated the advantage of ACDF in preserving the posterior muscles, thereby making postoperative axial pain less likely13). In the case of cervical arthroplasty, 25% of patients also reported neck and shoulder pains during follow-up period14).…”
Section: Discussionmentioning
confidence: 98%
“…They concluded that more than half (57%) of the patients recovered well after surgery, with still many patients experiencing chronic neck pain and physical dysfunction with decreased neck movement and strength. Another study on neck pain after ACDF was conducted by Matsumoto et al 13) , who reported that neck pain was observed in 25.8% of the ACDF patients at the follow-up period. No significant association was observed between neck pain and changes in the cross-sectional area of the posterior muscles over time.…”
Section: Discussionmentioning
confidence: 99%